2011
DOI: 10.1111/j.1464-410x.2011.10808.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and medical treatment of lower urinary tract symptoms in adult men: applying specialist guidelines in clinical practice

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Several sets of comprehensive treatment guidelines (national and international) exist for managing male lower urinary tract symptoms (LUTS), but these are not widely adopted in primary and secondary care, and are not consistently applied across Europe. This paper will improve the consistency of treatment approaches for adult males with LUTS by providing a clear, concise summary of existing treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…I am pleased to read that primary-care physicians tend to seek urology support when patients have severe LUTS (IPSS C20), large prostate glands, voiding symptoms suggestive of benign prostatic obstruction, and insufficient treatment response during initial therapy, and when physicians have little experience with LUTS/BPH patients. The common assessment practices in Portugal therefore appear to be compatible with the recommendations formulated by urologists in 2012, who defined the circumstances under which patients should be referred for specialized care [9].…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…I am pleased to read that primary-care physicians tend to seek urology support when patients have severe LUTS (IPSS C20), large prostate glands, voiding symptoms suggestive of benign prostatic obstruction, and insufficient treatment response during initial therapy, and when physicians have little experience with LUTS/BPH patients. The common assessment practices in Portugal therefore appear to be compatible with the recommendations formulated by urologists in 2012, who defined the circumstances under which patients should be referred for specialized care [9].…”
mentioning
confidence: 58%
“…It is therefore crucial to know when nonurologists should transfer their patients to specialized urology care. An expert panel recommended specialized urology support in particular when physicians are in doubt of the origin or benign character of LUTS, in cases of macroscopic hematuria, or in men with absolute indications for prostate surgery [9].Adherence to guidelines is crucial for every medical specialty dealing with LUTS/BPH because real-life practice in the USA has shown that doctors who follow guidelines perform significantly less prostate surgery than doctors who do not [10]. Doctors with poor adherence to guidelines will have performed prostate surgery within the first year of diagnosis in 11 % of patients, whereas doctors with good adherence to guidelines operated on only 2 % of their patients (which translates into a 91 % decrease in the adjusted odds of receiving surgery with good vs. poor guideline adherence).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lower urinary tract symptoms (LUTS) are a common problem in older men that increases steeply with age [1,2]. Approximately 50% of Enhanced content for Advances in Therapy articles is available on the journal web site: www.advancesintherapy.com men 70-80 years of age report moderate-tosevere LUTS, with significant bother, and impact on quality of life [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In general, a thorough history (with quantification of symptoms and quality of life issues; IPSS), a voiding chart (the physician should rule out nocturia, polyuria, and polydipsia), physical examination (with digital rectal examination of the prostate), urinalysis, determination of serum prostate-specific antigen (PSA), ultrasonography of the bladder, prostate, upper urinary tract (with determination of postvoid residual urine), and uroflowmetry provide all information needed for therapeutic decisions, at least on a nonsurgical level [2]. In men >50 years of age with an IPSS >7, no evidence of excessive nocturia, an enlarged prostate, maximum urinary flow rates <12 mL/sec, and postvoid residual urine <150 mL, BPO resulting from prostatic enlargement is the most likely cause of the problem [14].…”
Section: Introductionmentioning
confidence: 99%